ANALISIS KEPUTUSAN INVESTASI GEN Z MELALUI LITERASI KEUANGAN DAN RISK TOLERANCE - Muhammad Milzam; Mohammad Sigit Taruna; Muhammad Shofiyuddin (Jurnal GeoEkonomi, 2024)
Investment is a financial activity that requires consideration of complex financial aspects. This research aims to analysing financial decision making of youth generation especially Gen Z through the financial literacy and risk tolerance. This research uses primary data by conducting a survey using a questionnaire to members of the Karang Taruna Sumur Jongglang Bogo Village who are under 26 years old (Gen Z). The data of this research comes from Likert scale. Also, this research using SPSS analysis software 26th version to proceed the data from 30 respondents. Based on the multiple linear regression test, find that financial literacy has no significant effect on investment decisions, while risk tolerance has a significant positive effect on investment decisions of Gen Z. However, the results of the goodness of fit test shows that financial literacy and risk tolerance was fit and good research models for analysing investment decisions. Based on the research results, it can be concluded that Gen Z already has good financial literacy but is not yet able to support good investment decisions. Besides, high risk tolerance creates a better investment decision making.